THE NUTRITIVE EFFECT OF SOME FUNGAL POLYSACCHARIDES USED ON BROILER FEEDING - TATIANA RUGEA; E. TÎRZIU; R.V. GROS; MONICA SERES (Scientific Papers Animal Science and Biotechnologies, 2023)
In this study we determined the immunostimulant effect of an alcoholic total extract from Pleurotus ostreatus administered in 5 and 15% concentration to broiler chickens vaccinated against infectious bursal disease. The immunogen was represented by two vaccines (Biavac and Biaromvac) used in infectious bursal disease prophylaxis. Vaccination was made at the age of seven days in four groups of broilers. Laboratory tests results showed that fungal extract have a stimulant action upon average daily gain, the most conclusive results being registered in group treated with 15% Pleurotus extract.